2008
DOI: 10.1002/pat.1310
|View full text |Cite
|
Sign up to set email alerts
|

A review on ternary immiscible polymer blends: morphology and effective parameters

Abstract: In this paper a review of studies on ternary polymer blends, reported in the period from 1980s to 2007, is presented. This review covers the investigations carried out on the formation of morphologies observed in ternary blends including separated disperse, core–shell and co‐continuous morphologies; and also the parameters affecting the type of morphology and its distribution state. Copyright © 2008 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 74 publications
2
46
0
1
Order By: Relevance
“…These blends were mostly prepared through melt blending and solution mixing methods. Regardless of the preparation method used, the morphologies of the blends were found to depend on the ratios of the components in the blend, their viscosities, and the interfacial tension between the component phases [27,48]. Depending on the PCL/PBS blend ratios, the minor component generally formed discrete spherical domains in a matrix of the major component, which indicates poor interfacial interactions between the components.…”
Section: Pcl/pbs Blends 21 Morphologymentioning
confidence: 99%
“…These blends were mostly prepared through melt blending and solution mixing methods. Regardless of the preparation method used, the morphologies of the blends were found to depend on the ratios of the components in the blend, their viscosities, and the interfacial tension between the component phases [27,48]. Depending on the PCL/PBS blend ratios, the minor component generally formed discrete spherical domains in a matrix of the major component, which indicates poor interfacial interactions between the components.…”
Section: Pcl/pbs Blends 21 Morphologymentioning
confidence: 99%
“…of polymer blends has long been a research focus. [1][2][3][4] Basically, there are three kinds of phase structures in ternary systems: (1) the components of the dispersed phases are dispersed separately; (2) one component is encapsulated by another component, forming core-shell particles dispersed in the third phase; (3) in an intermediate state, partial encapsulation of one dispersed component by another one could occur. [4][5][6][7][8][9][10] Hobbs et al [7] showed that the morphology of ternary blends can be predicted through knowledge of the interfacial tension between the components of the blends.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Melt blending of two or more polymers is a collaborative approach to develop new material with customized properties. 3,4 Prediction, control and study of morphology and mechanical properties in polymer blend especially in ternary polymer blend are a difficult task. 5,6 Generally the morphology of a ternary polymer blend is depended on interaction parameters among three components, rheological properties of the components and processing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of ternary polymer blends was first reported in the 1980s by Hobbs et al 3,12,13 In particular, they used the concept of spreading coefficient and rewrote Harkin's equation in which two distinct phases are dispersed in a matrix phase to predict the morphology of ternary blends. In a ternary blend of 폴리머, 제38권 제4호, 2014년 three polymers A, B, and C, the spreading coefficient, λ ijk , can be defined as eq.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation